Insomnia as a benign presentation of fatal familial insomnia (FFI). A case report from Malaysia - Kiat, Richard Teo Soon; Chung, Law Wan (Asian Journal of Medical Sciences, 2021)
Fatal familial insomnia (FFI) is an extremely rare autosomal dominant prion disease. The chief clinical features include an organic sleep disorder associated with sympathetic overdrive, motor and bulbar compromise as well as progressive cognitive decline. Death ensures in 100% of cases with a mean survival duration of 18 months from time of symptom onset. Treatment strategies in the management of FFI remains largely symptomatic with greater emphasis placed on palliative care services. We report a case of a 31-year old gentleman (Mr G) who presented with insomnia, sleep behavior disturbances, diplopia, myoclonus and transient global amnesia. A family history of a paternal aunt with similar presentation who passed away raised the suspicion of probable FFI, which was subsequently confirmed by genetic testing. Mr G is the first reported definitive FFI case of Malaysian Chinese descent. Standard MRI imaging and CSF analyses are insufficient in the workup of an individual with probable FFI. PET scan, polysomnogram and genetic studies are required for cases with high index of suspicion. In view of the rapid progression of the disease with significant cognitive impairment within months of symptom onset, we advocate for early diagnosis and a biopsychosocial patient-centered treatment approach.